Measurement of the Planck constant at the National Institute of Standards and Technology from 2015 to 2017. (28th July 2017) - Haddad, D; Seifert, F; Chao, L S; Possolo, A; Newell, D B; Pratt, J R; Williams, C J; Schlamminger, S
Abstract: Researchers at the National Institute of Standards and Technology (NIST) have measured the value of the Planck constant to be h = 6.626 069 934 ( 89 ) × 10 − 34 J s (relative standard uncertainty 13 × 10 − 9 ). The result is based on over 10 000 weighings of masses with nominal values ranging from 0.5 kg to 2 kg with the Kibble balance NIST-4. The uncertainty has been reduced by more than twofold relative to a previous determination because of three factors: (1) a much larger data set than previously available, allowing a more realistic, and smaller, Type A evaluation; (2) a more comprehensive measurement of the back action of the weighing current on the magnet by weighing masses up to 2 kg, decreasing the uncertainty associated with magnet non-linearity; (3) a rigorous investigation of the dependence of the geometric factor on the coil velocity reducing the uncertainty assigned to time-dependent leakage of current in the coil.